Dexrazoxane for cardioprotection in older adults with acute myeloid leukemia. (2017) - Vachhani, Pankit; Shin, Sarah; Baron, Jeffrey; Thompson, James E.; Wetzler, Meir; Griffiths, Elizabeth A.; Ontiveros, Evelena P.; Spangenthal, Edward J.; Wang, Eunice S.
Abstract: Anthracyclines constitute the backbone of intensive adult acute myeloid leukemia (AML) therapy. Cardiotoxicity is one of its most serious adverse effects, and its incidence increases with cumulative dose. Dexrazoxane is a cardioprotective agent used in conjunction with anthracycline therapy. There is limited data of its usage in adult AML patients. We report the outcomes of six older adults at high risk of anthracycline-induced cardiotoxicity who received dexrazoxane during induction/re-induction therapy. Five had preserved left-ventricular function while two proceeded onto stem-cell transplantation. Additional investigation of dexrazoxane in adult leukemia therapy is warranted, particularly in older patients at highest risk for cardiovascular mortality.